A steerable pyramid autoencoder based framework for anomaly frame detection of water pipeline CCTV inspection - Jiao, Yutong; Rayhana, Rakiba; Bin, Junchi; Liu, Zheng; Wu, Angie; Kong, Xiangjie (Measurement : journal of the International Measurement Confederation, 2021)
Closed-circuit television (CCTV) is being widely adopted in water pipeline inspection. The inspector needs to spend a long time to watch the recorded video during the office-based survey and can get fatigue easily. An automated process can release the inspector’s work load and ensure the consistent quality of the survey. However, a fully automated survey of varied structural discontinuities still remains as a challenge. This study aims to first identify the anomaly frames of the CCTV video, which contain the major anomalies captured from the internal surface of the pipe. Thus, the inspector can focus more on these anomaly frames. In this paper, an anomaly frame detection framework based on steerable pyramid autoencoder (SPAE) is proposed. The SPAE can generate discriminative representations to be used in the prediction. Both the parameter optimization and comparative studies for the proposed SPAE were carried out in this research. The experimental results demonstrate that this novel SPAE algorithm can achieve 0.984 accuracy and 0.984 F1-score, which outperforms other state-of-the-art methods selected for comparison. Thus, the proposed framework can significantly improve the accuracy and efficiency for anomaly frame detection, which will highly facilitate the pipeline condition assessment through the CCTV inspection. [Display omitted] •The paper proposes a steerable pyramid autoencoder based framework.•Anomaly frame detection is conducted on closed-circuit television videos.•The framework significantly facilitates the water pipeline condition assessment.•Steerable pyramid is integrated into the autoencoder based network.•The method develops great capability of representation learning and extraction.